Analisis Bibliometrik Publikasi Perkembangan Artificial Intelegent (AI) dalam Dunia Pendidikan - Arianti, Juli; Oktaviani, Mutiya; Najdah T, Najdah T; Sinambela, Yohannes Putra Perkasa (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The aim of this research is to examine the development of publications related to Artificial Intelligence (AI) in the world of education. This research uses bibliometric analysis with the keyword